Holistic Optimization toward Ultrathin Flexible Perovskite Solar Cells with High Efficiency and Mechanical Robustness - Guanqi Tang; Fangyuan Zheng; Jiajun Song; Qidong Tai; Jiong Zhao; Feng Yan (Advanced Science)
Abstract An ultrathin and flexible perovskite solar cell (f‐PSC) is highly desirable as a portable power source, while the rigidity of key components including perovskite and transparent electrode of a device leads to challenges in fabrication. Here, several approaches are developed to improve the mechanical flexibility and photovoltaic performance of ultrathin f‐PSCs. First, a two‐dimensional perovskite with low Young's modulus is introduced at the boundaries of perovskite films as a lubricant to release stress which is confirmed by in situ TEM characterization. Second, conductive PEDOT:PSS doped with sucralose is used as a transparent electrode to enhance the mechanical flexibility and photovoltaic performance of the device. Third, an ultrathin PET substrate is employed to shift the neutral plane into the perovskite film which further improves the mechanical flexibility of devices. Consequently, an ultrathin f‐PSC is successfully fabricated with a power conversion efficiency of 21.44% and a record power‐per‐weight value of 47.8 W g−1. A stretchable device is realized by laminating the ultrathin f‐PSC on a pre‐strained substrate, which shows stable performance when it is stretched up to 40%. The f‐PSC shows a high efficiency of 36.25% under room light intensity, suggesting great potential for indoor photovoltaic application.